Institutions and Values: A Methodological Inquiry. Issue 2 (2nd April 2016) - Natarajan, Tara; Edwards, Wayne
Abstract: Economics entails a study of institutions regardless of the school of thought, and it is inherently an analysis of institutional transformation with a vision toward creating positive social change through economic arrangements. However, the conceptions of institutions, identity of individuals, human nature as it pertains to economics, identification of the economic sphere, its concerns, and studying its evolution, all vary substantively across schools of thought. We examine the following issues: (i) the differences in the ontological identity of the individual between heterodox approaches, new institutional economics (NIE), and the neoclassical school; (ii) the central point of divergence between original institutional economics (OIE) and NIE, despite both schools being committed to the project of an "institutionally" centered approach to economics; and (iii) the absence of a cohesive project to explore foundational theoretical congruencies among those heterodox approaches that have a shared vision, values, and a common ontological identity of socially embedded people.